2022
DOI: 10.21203/rs.3.rs-1811273/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Five-port Integrated Planar Ultra Wideband and Narrowband Antennas System Using Excitation Switching Reconfigurable Technique for Cognitive Radio Applications

Abstract: This work presents an integrated planar five-element antennas system for cognitive radio (CR) applications. The proposed system is composed a ultra-wideband (UWB) antenna for sensing the radio spectrum and four different narrowband (NB) antennas for conducting the communication tasks. The overall antenna system is printed on FR-4 substrate of 50 mm × 50 mm × 1.6 mm dimension. The UWB antenna-coupled at port 5 (P5) is designed for sensing the 3.1 GHz to 10.6 GHz un-licensed UWB band. The first NB antenna attach… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Table 2 represents the comparative study between recently reported multi-port antennas with diferent functionalities [46][47][48][49][50][51]. For a fair comparison, here, CR antennas with similar objectives are considered.…”
Section: Comparison With Previously Reported Workmentioning
confidence: 99%
“…Table 2 represents the comparative study between recently reported multi-port antennas with diferent functionalities [46][47][48][49][50][51]. For a fair comparison, here, CR antennas with similar objectives are considered.…”
Section: Comparison With Previously Reported Workmentioning
confidence: 99%